Comprehensive Cardiovascular Medicine in the Primary Care Setting - Toth, Peter P.; Cannon, Christopher P.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
Comprehensive Cardiovascular Medicine in the Primary Care Setting provides an authoritative, detailed discussion of cardiovascular disease balanced with practical utility. Disease states are explained with emphasis on risk factors, risk estimation, and established cardiac disease. The book also delves into the co-morbid conditions which surround cardiovascular disease, including peripheral vascular disease, chronic kidney disease, depression, and erectile dysfunction, with the goal of improving quality of life for affected individuals. An abundance of algorithms, case studies, and recommendations on evidence-based best practices facilitate rapid learning. A key resource for the busy practitioner, this book is designed to give the reader the skills to confidently perform assessments, initiate and maintain efficacious therapy, and know when a referral to a cardiologist is advisable.
1. Cardiovascular Epidemiology and Characterization of Atherosclerotic Disease Risk Factors -- 2. Atrial Hypertension -- 3. Management Dyslipidemia -- 4. Obesity and Therapeutic Approaches to Weight Loss -- 5. Inflammatory Markers and Novel Risk Factors -- 6. Deciphering Cardiovascular Genomics and How They Apply to Cardiovascular Disease Prevention -- 7. The Metabolic Syndrome: 2009 -- 8. Chronic Kidney Disease in the Primary Care Setting -- 9. Evaluation of Chest Pain and Myocardial Ischemia -- 10. Unstable Angina and Non-ST Elevation Myocardial Infarction -- 11. ST Elevation Myocardial Infarction -- 12. Coronary Artery Stenting -- 13. Coronary Artery Bypass Grafting -- 14. Cardiac Rehabilitation -- 15. Carotid Artery Disease -- 16. Peripheral Arterial Disease -- 17. Deep Venous Thrombosis and Pulmonary Embolism -- 18. Pulmonary Hypertension and Cor Pulmonale -- 19. Diagnosis and Management of Ischemic Stroke -- 20. Aortic Aneurysms -- 21. Erectile Dysfunction -- 22. Valvular Heart Disease -- 23. Pericardial Diseases -- 24. Common Atrial and Ventricular Arrhythmias -- 25. Evidence-based Management of the Patient with Congestive Heart Failure -- 26. Coronary Calcium Scoring -- 27. Cardiac Computed Tomography -- 28. Cardiac Magnetic Resonance Imaging.
Keywords: Medicine; Family medicine; Internal medicine; Cardiology; Nursing; Medicine & Public Health; Internal Medicine; Cardiology; General Practice / Family Medicine; Nursing